STUDI KLINIK EFEK SEDUHAN FORMULA JAMU HIPERTENSI TERHADAP FUNGSI GINJAL - Agus Triyono; Fajar Novianto (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Clinical study on the effect of hypertension herbs steeping formula on the renal functions has been done. Hypertension herb formula consists of Apium graveolens L.; Orthosiphon spicatus (Thunb.); Centella asiatica (L.); Curcuma xantoriza; Phyllantus niruri, and Curcuma domestica. Clinical trials were conducted by open-label clinical trial and pre-post test design. Thirty human subjects who have met the inclusion and exclusion criteria were involved in this study. The study protocol was approved by the research ethics of Ethics Committee for Health Research, National Institute of Health Research and Development, Ministry of Health. Before the treatment, the subjects who had signed informed consent performed anamnesis, medical history, clinical symptoms, physical examination and laboratory tests of renal function (BUN and creatinine levels). The subjects treat with the hypertension herbs steeping formula three times a day for eight weeks, then controlled it once a week. Anamnesis on the clinical symptoms, the possibility of side effects and physical examination diagnostic on the subject performed every week. Measurement on the renal function performed every four week. Base on the anamnesis and physical examination, the clinical study concluded that there were no significant adverse effects on the subject. Paired t-test results showed that there was no significant difference on subject’s BUN and creatinine levels before and after the treatment hypertension herbs steeping formula on the 28th and 56th day (p <0.05). Clinically, the treatment of hypertension herb steeping formula for 56 days did not affect the subject’s renal function. Key words: Hypertension herbs steeping formula, renal function